Plan estratégico de marketing para la introducción al mercado Guayaquileño de las maquinas expendedoras (vending machines) de café - Triviño Moscoso, Jacqueline (2009)
This work will enable us to meet acceptance Strategic marketing plan for the Guayaquil market introduction of vending machines (vending machines) of coffee. . For this information was obtained through market research that was conducted in the city of Guayaquil. Based on information we obtained we decided to locate the coffee vending machines at strategic points in the clinic as dawn and Policentro Kennedy, ESPOL Mall Prosperino and rocks and the sun to enter the market more accurately and satisfy their needs. For the assessment of the future results of Ecuador Glassware financial projections were used. As we see in the sensitivity analysis of variations in sales with respect to changes to input costs are higher. The sensitivity analysis shows the company must focus on not decrease their sales, and that much more important is the business approach that the agreements that the company may have with suppliers in the marketing of inputs at lower cost as the project is entirely feasible in the short term